Dissolved organic compounds with synchronous dynamics share chemical properties and origin. Issue 11 (30th September 2021) - Merder, Julian; Röder, Heidelinde; Dittmar, Thorsten; Feudel, Ulrike; Freund, Jan A.; Gerdts, Gunnar; Kraberg, Alexandra; Niggemann, Jutta
Abstract: The temporal dynamics of dissolved organic matter (DOM) are inherently linked with the functioning of aquatic ecosystems. Because DOM represents a complex mixture of millions of different compounds, the statistical analysis of DOM dynamics poses a huge challenge. Here, we present a statistical approach based on hierarchical clustering of time series that groups DOM compounds with synchronous dynamics. We applied this approach to time series of Fourier‐transform ion cyclotron resonance mass spectrometry data of DOM sampled over a period of 26 months near Helgoland, an island in the Southern North Sea. We identified three DOM clusters, which represented a total of 1392 different molecular formulae and showed distinct chemical properties and noticeably compound matches within the PubChem database. Correlations of the three DOM clusters with abundance data of prokaryote and phytoplankton species and with environmental parameters provided consistent indications on the potential origin of the clustered compounds. The first cluster integrated terrestrial DOM originating from riverine discharge reaching Helgoland waters. The second cluster was attributed to DOM related to phytoplankton and microbial activity, whereas the third cluster was interpreted as representing the marine refractory DOM background. Accordingly, while further partitioning divided each of the first two clusters into five sub‐clusters with distinct temporal dynamics and molecular characteristics, the third cluster persisted as a stable feature. Applying a purely mathematical approach, we thus confirmed the differential dynamics of individual DOM compounds and compound groups and showed that temporal dynamics of dissolved molecules are linked to their origin and transformation history.